HUBUNGAN SIKAP DAN POLA KOMUNIKASI ORANG TUA DENGAN PERILAKU SEKS PRANIKAH PADA SISWA SMA DI KOTA SAMARINDA TAHUN 2015 - Nur Rohmah (Universitas Widya Gama Mahakam Samarinda, 2016)
Base on various reports, stated that many teens already trapped in unhealthy reproductive behavior, including sexual behavior before marriage. Based on the survey results Indonesian Family Planning Association (IPPA) East Kalimantan in 2008. Of the 300 adolescents (aged 13-20 years) 12% of respondents claimed to have had sex. This study aims to determine the relationship Attitudes and Patterns of Communication With Parents with Premarital Sex Behavior in High School Students in Private Samarinda in 2010. This study is observational method